Machine learning models predict the emergence of depression in Argentinean college students during periods of COVID-19 quarantine - López Steinmetz, Lorena Cecilia (2024)
Fil: López Steinmetz, Lorena Cecilia. Universidad Nacional de Córdoba. Facultad de Psicología; Argentina.